Green entrepreneurship challenges and business growth among the selected sectors - Mohamad, Norhidayah; Hamiza, Nur Amielin Aisyah; Juma'at, Elly Julieanatasha; Othman, Azrina; Md Isa, Mohamed Hafiz; Samsudin, Norsamsinar (Research and Scientific Innovation Society, 2025)
Green entrepreneurship plays a vital role in promoting sustainable development in Malaysia; however, entrepreneurs encounter barriers that constrain its growth. This study examines the impact of regulatory, financial, market, technological, and infrastructure barriers, as well as knowledge management barriers, on business growth across renewable energy, sustainable agriculture, and eco-friendly product sectors. Using a quantitative approach, data from 376 entrepreneurs were analysed through ANOVA and multiple regression. Results show significant sectoral differences for regulatory (p = 0.035) and financial barriers (p = 0.033). The model explained 60.7% of the variance in business growth (R² = 0.607). All barriers significantly affected growth, with financial (β = 0.443) and regulatory (β = 0.188) showing the strongest influence, while knowledge management had a negative effect (β = –0.141). The findings imply an urgent need for streamlined regulations, targeted financial mechanisms, enhanced technological infrastructure, and stronger knowledge management systems to support innovation, competitiveness, and long-term sustainability in Malaysia’s green entrepreneurship ecosystem.